Optimal Low-Frequency Parameter of Percutaneous Electrical Nerve Stimulation in Patients with Lower Back Pain: A Pilot Study - Roberto San-Emeterio-Iglesias; Carlos Romero-Morales; Francisco Minaya-Muñoz; Blanca De-la-Cruz-Torres (Life, 2025)
Background: The methodology of ultrasound (US)-guided percutaneous neuromodulation (PNM) remains unclear. Objective: To determine the optimal stimulation frequency (3 Hz vs. 10 Hz) during the short-term application of US-guided PNM on the sciatic nerve, we assessed the therapeutic benefits, including pain reduction, hip passive internal rotation range of motion (IR-ROM), balance, and functionality, in patients with chronic low back pain (LBP). Methods: Forty patients with LBP were randomly assigned to two groups, each receiving isolated percutaneous electrical stimulation of the sciatic nerve. One group received stimulation at 3 Hz, while the other received stimulation at 10 Hz. Pain intensity, hip passive IR-ROM, hip muscle strength, and the Oswestry Disability Index (ODI) were measured before and one week after the intervention. Results: Both interventions significantly reduced pain and improved ROM, balance, and functionality after one week (p = 0.001). However, significant between-group (treatment × time) differences were observed for pain intensity (p = 0.001) and flexion strength in the non-intervention limb (p = 0.01), though the effect size was small (η2 = 0.1). Conclusions: US-guided PNM applied to the sciatic nerve was more effective at 3 Hz than at 10 Hz in relieving pain intensity in patients with LBP.